"Bold Distinguished You" : a critical discourse analysis of the representation of masculinity in Destiny Man, 2012 - 2013 - Hutcheson, Lauren (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2015)
Radical social and economic changes have transformed the employment opportunities available to black men in South Africa, and consumer magazines like Destiny Man have been quick to respond. Historical shifts in the configuration of an ideal black masculinity have been proposed over time in magazine representations of black men. Critiques of the representations of black men in consumer magazines pre- and post- independence interrogate the politics of the ways in which black masculinity has been, and is, configured around classed identities. In this study, I present the findings of a critical discourse analysis (CDA) on the construction and representation of masculinity within a contemporary South African's men's lifestyle magazine, Destiny Man. This study presents an analysis of the subject positions that this magazine constructs for its male readers. Destiny Man proposes particular kinds of discursive subjects in its sets of representations, both in word and image. The images and copy validate a neo-liberal elite masculinity achieved through self-surveillance and a variety of technologies of self, with the ultimate focus on material success. I argue that these representations have implications for the development of masculinities in a context marked by extreme inequality.
Keywords: Uncatalogued